Btg1 is Required to Maintain the Pool of Stem and Progenitor Cells of the Dentate Gyrus and Subventricular Zone - Farioli-Vecchioli, Stefano; Micheli, Laura; Saraulli, Daniele; Ceccarelli, Manuela; Cannas, Sara; Scardigli, Raffaella; Leonardi, Luca; Cinà, Irene; Costanzi, Marco; Ciotti, Maria Teresa; Moreira, Pedro; Rouault, Jean-Pierre; et al. (Frontiers in Neuroscience, 2012)
Btg1 belongs to a family of cell cycle inhibitory genes. We observed that Btg1 is highly expressed in adult neurogenic niches, i.e., the dentate gyrus and subventricular zone (SVZ). Thus, we generated Btg1 knockout mice to analyze the role of Btg1 in the process of generation of adult new neurons. Ablation of Btg1 causes a transient increase of the proliferating dentate gyrus stem and progenitor cells at post-natal day 7; however, at two months of age the number of these proliferating cells, as well as of mature neurons, greatly decreases compared to wild-type controls. Remarkably, adult dentate gyrus stem and progenitor cells of Btg1-null mice exit cell cycle after completing the S phase, highly express p53 and p21, and within 5 days undergo apoptosis. In SVZ we observed an equivalent decrease, associated to apoptosis, of Btg1-null stem cells, neuroblasts and neurons; furthermore, neurospheres derived from SVZ stem cells showed an age-dependent decrease of the self-renewal and expansion capacity. We conclude that the ablation of Btg1 reduces the pool of dividing adult stem and progenitor cells in dentate gyrus and SVZ by decreasing their proliferative capacity and inducing apoptosis, likely reflecting the impairment of the control of the cell cycle transition from G1 to S phase. As a result, the ability of Btg1-null mice to discriminate among overlapping contextual memories was affected. Thus, Btg1 appears to be required for maintaining adult stem and progenitor cells quiescence and self-renewal.